Smokeless tobacco and its dependence among the urban-slum population of Jodhpur city - Joshi, Vibha; Chakraborty, Sourabh; Joshi, Nitin Kumar; Bajaj, Komal; Sati, Bhawana; Purohit, Anil (International Journal Of Community Medicine And Public Health, 2021)
Background: Socio-economic status can be an important determinant for patterns of tobacco consumption and its related health risks. Easy availability and affordable price may lead to the indulgence of smokeless tobacco; this deprived the section of society towards addiction of smokeless tobacco. Therefore, this study was conducted to ascertain smokeless tobacco use and its dependence in urban slum population of Jodhpur city. Methods: A cross-sectional survey was conducted in the urban-slum population of Jodhpur in 2019. A cluster sampling strategy was used to collect data from 1200 participants in different slums of Jodhpur city. The semi-structured questionnaire was used to obtain information on tobacco usage and willingness to quit. Results: Out of surveyed 1200 participants, 48.5% were males and 51.4% were females. 65.7% of the tobacco users reported in study population. Among tobacco user’s majority were using smokeless tobacco (75.4%), followed by 14.8% dual tobacco users and 9.8% were smoking tobacco. Out of female and male tobacco users, 95% females and 86.3% males were using smokeless forms of tobacco respectively. The frequency of daily tobacco use, time of tobacco chewing, duration of tobacco use was significantly associated with gender. No significant association was found between willingness to quit and gender. Conclusions: Smokeless tobacco was prevalent as compared to smoking form in urban-slums of Jodhpur city. Younger population and women were more attracted towards smokeless tobacco and willingness to quit tobacco was equally prevalent among males and females. An effective health education strategy for tobacco cessation should be designed according to age and gender of urban-slums.